2023
DOI: 10.1002/adfm.202214613
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Unhybridized O 2p Orbitals of High‐Performance Li‐Rich Mn‐Based Layered Oxide Cathode by Gd‐Doping Induced Bulk Oxygen Vacancies

Abstract: Li-rich Mn-based layered oxides (LRLOs) with ultrahigh specific capacities are promising cathode materials for high energy density lithium-ion batteries. Nevertheless, severe irreversible oxygen release, structure degradation, capacity and voltage attenuation hinder their commercialization due to the uncontrollable oxygen redox chemistry originated from unhybridized O 2p orbitals. Herein, a strategy to generate bulk oxygen vacancies is proposed. And bulk oxygen vacancies are constructed by lowering the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…[20] Han's group proposed that Vo reduced the energy level and the number of unhybridized O 2p states, which effectively delayed the oxygen-redox behaviors and inhibited the oxygen loss. [21] The inhibitory effect of Vo on oxygen release was also reported by Liu and co-workers, who found that Vo could tune the d-d Coulombic interactions (terms U) in Li 1.2 Mn 0.6 Ni 0.2 O 2-δ through a small amount of Mn 3 + (Figure 3a). [22] The decreased U prevented more oxygen escape and ensured the reversible anionic redox reaction.…”
Section: Ligand Structuresupporting
confidence: 69%
See 1 more Smart Citation
“…[20] Han's group proposed that Vo reduced the energy level and the number of unhybridized O 2p states, which effectively delayed the oxygen-redox behaviors and inhibited the oxygen loss. [21] The inhibitory effect of Vo on oxygen release was also reported by Liu and co-workers, who found that Vo could tune the d-d Coulombic interactions (terms U) in Li 1.2 Mn 0.6 Ni 0.2 O 2-δ through a small amount of Mn 3 + (Figure 3a). [22] The decreased U prevented more oxygen escape and ensured the reversible anionic redox reaction.…”
Section: Ligand Structuresupporting
confidence: 69%
“…demonstrated that Vo shortened the TM‐O bond lengths in P2‐Na 0.7 Mn 0.75 Ni 0.25 O 2 , resulting in strong ionic character of TM‐O bonds and thus improving the structural stability [20] . Han's group proposed that Vo reduced the energy level and the number of unhybridized O 2 p states, which effectively delayed the oxygen‐redox behaviors and inhibited the oxygen loss [21] . The inhibitory effect of Vo on oxygen release was also reported by Liu and co‐workers, who found that Vo could tune the d ‐ d Coulombic interactions (terms U ) in Li 1.2 Mn 0.6 Ni 0.2 O 2‐δ through a small amount of Mn 3+ (Figure 3a).…”
Section: Structural Modulation Of Vo In Ltmosmentioning
confidence: 99%
“…1c displays the electron paramagnetic resonance (EPR) spectra of the samples, with peak intensity positively correlated with the oxygen vacancy content ( g = 2.002). 31 Remarkably, MnO@Cs exhibits the highest concentration of oxygen vacancies, attributable to the formation of vacancies during the oxidation with potassium permanganate and calcination processes. Conversely, CeO 2 @Cs displays the lowest concentration of oxygen vacancies, possibly due to the loading of Ce species stabilizing the lattice structure of CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the bandgap of HE-KMO is reduced, which is expected to enhance the electronic conduction and electrochemical performance of HE-KMO. 27,28 Based on the partial DOS of HE-KMO, shown in Figure 1b, Mn 3d, Ni 3d, Fe 3d, Co 3d, and Cu 3d electron densities imply that these TMs can participate in the charge compensation due to the electron occupation near Fermi energy, while Ti and Mg are inactive. Additionally, the electronic structures of Mn 3d in HE-KMO (Figure 1b) is obviously different from that of Mn 3d in KMO (Figure 1c), suggesting that multielement doping in high-entropy oxides can modulate the electronic structure of both overall material and specific atoms in layered oxide cathodes.…”
Section: Resultsmentioning
confidence: 99%